Evaluation of Sound Perception to Identify Candidate Frequency for Wireless Networking ; Chapter In : New Trends in Networking, Computing, E-learning, Systems Sciences, and Engineering - Mathew, Kuruvilla; Tan, Chong Eng; Biju, Issac (Springer International Publishing, 2015)
Wireless technology has been introduced and growing since early twentieth century, but there are still environments the current technologies find it difficult to penetrate. The dense jungle terrain, for example, pose a huge challenge for the 0.12 m wavelength of the Wi-Fi signals, but the FM radio frequency signals at a wavelength of 3 m function a lot better. This paper studies the possibility of using a very low frequency, down to the range of audible frequencies to try and identify the frequency band that can be used, ubiquitously and unobtrusively. Sound can be considered as a ubiquitous signal due to obvious reasons and the search is to find the unobtrusive frequency band that can be a candidate frequency for data carrier signals. The paper is presented in two sections, the first section does a geographically and age neutral survey to identify the unobtrusive signal and second section analyses the noise profiles in these frequency bands